Use of Disinfectants and Cleaning Products Associated with Respiratory Disease: A Scoping Review (Epidemiology, Biostatistics, and Public Health, 2024)
Introduction: there is extensive evidence on the harmful respiratory effects of exposure to disinfectants and cleaning products. Methodology: an exploratory systematic review was carried out in five databases: LILACS, PubMed, MEDLINE and BIREME. Twenty articles from 2013 to 2024 were selected for the present review. Results: chemical compounds present in some disinfectants and cleaning products such as Polyhexamethylene guanidine (PHMG) and Chloromethylisothiazolinone/Methylisothiazolinone (CMIT/MIT) influence the development of Humidifier Respiratory Distress Syndrome (HDRS) and increased incidence of asthma and Chronic Obstructive Pulmonary Disease (COPD) in adults. Conclusions: There is a relationship between exposure to chemical compounds in certain disinfectants and lung health impairment. It is imperative to increase the general population’s awareness of the effects of these substances will lead to improved self-care in those who are in daily contact with these elements.
Keywords: Respiratory Tract Diseases; Disinfectants; Asthma; Chronic Obstructive Pulmonary Disease